2021
DOI: 10.3390/ph14090901
|View full text |Cite
|
Sign up to set email alerts
|

Caesalpinia mimosoides Leaf Extract Promotes Neurite Outgrowth and Inhibits BACE1 Activity in Mutant APP-Overexpressing Neuronal Neuro2a Cells

Abstract: Alzheimer’s disease (AD) is implicated in the imbalance of several proteins, including Amyloid-β (Aβ), amyloid precursor protein (APP), and BACE1. APP overexpression interferes with neurite outgrowth, while BACE1 plays a role in Aβ generation. Medicinal herbs with effects on neurite outgrowth stimulation and BACE1 inhibition may benefit AD. This study aimed to investigate the neurite outgrowth stimulatory effect, along with BACE1 inhibition of Caesalpinia mimosoides (CM), using wild-type (Neuro2a) and APP (Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…The real-time PCR assay was performed using AccuPower 2X GreenStar™ qPCR Master Mix (Bioneer) in Exicycler™ 96 (Bioneer) using gene-specific primers ( Table 3 ). The mRNA expression level was calculated via the delta-delta Ct method using GAPDH as an internal control ( Rangsinth et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The real-time PCR assay was performed using AccuPower 2X GreenStar™ qPCR Master Mix (Bioneer) in Exicycler™ 96 (Bioneer) using gene-specific primers ( Table 3 ). The mRNA expression level was calculated via the delta-delta Ct method using GAPDH as an internal control ( Rangsinth et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Co-crystal structures of Kelch-like ECH-associated protein 1 (KEAP1) complexed with 2-[[4-[2-hydroxy-2-oxoethyl-(4-methoxyphenyl)sulfonyl-amino]-3-phenylmethoxy-phenyl]-(4-methoxyphenyl)sulfonyl-amino]ethanoic acid (GX8) (PDB ID: 6HWS, , accessed on 23 August 2021) and PTEN-induced kinase 1 (PINK1) complexed with ubiquitin (PDB ID: 6EQI, , accessed on 23 August 2021) [ 24 ], and E3 ubiquitin–protein ligase parkin (PDB ID: 5C1Z, , accessed on 23 August 2021) [ 25 ] were obtained from RCSB Protein Data Bank. Protein and compound files were prepared following the previous procedure [ 26 ]. Briefly, the proteins were prepared by removing all waters and original ligands, as well as adding missing hydrogen atoms and Kollman charges using the AutoDockTools-1.5.6 program.…”
Section: Methodsmentioning
confidence: 99%
“…[24], and E3 ubiquitin-protein ligase parkin (PDB ID: 5C1Z, https://www.rcsb.org/structure/5C1Z, accessed on 23 August 2021) [25] were obtained from RCSB Protein Data Bank. Protein and compound files were prepared following the previous procedure [26]. Briefly, the proteins were prepared by removing all waters and original ligands, as well as adding missing hydrogen atoms and Kollman charges using the AutoDockTools-1.5.6 program.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Many studies with herbal extracts have identified increased neurite outgrowth 10 as a potential feature of the herb's neuroprotective properties. 11,12 Thai medicinal herb Streblus asper Lour. (SA) Has previously been shown to protect against photoaging and provide neuroprotection in C.elegans.…”
Section: Introductionmentioning
confidence: 99%